2019
DOI: 10.3390/nano9040620
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Dependent Confinement Effect of Ionic Liquids in Porous Silica

Abstract: The effect of confining ionic liquids (ILs) such as 1-ethyl-3-methylimidazolium tetrafluoroborate [C2C1Im][BF4] or 1-butyl-3-methylimidazolium tetrafluoroborate [C4C1Im][BF4] in silica matrices was investigated by high-pressure IR spectroscopy. The samples were prepared via the sol-gel method, and the pressure-dependent changes in the C–H absorption bands were investigated. No appreciable changes were observed in the spectral features when the ILs were confined in silica matrices under ambient pressure. That i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In comparison with pure [C 4 MIM][PF 6 ] at the pressure of 0.4 GPa (Figure 2b), the C 2 -H and C 4,5 -H absorption bands of [C 4 MIM][PF 6 ]/DNA mixture at 0.4 GPa (Figure 3b) show smaller frequency shifts under compression. Previous studies [26][27][28] revealed that high pressure can enhance the cluster structure interaction and lead to a band frequency shift. The hydrogen-bond network of an IL cluster structure may be disrupted, as some added molecules (such as DNA) may disturb the associations of ILs or cut large aggregations to small pieces.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In comparison with pure [C 4 MIM][PF 6 ] at the pressure of 0.4 GPa (Figure 2b), the C 2 -H and C 4,5 -H absorption bands of [C 4 MIM][PF 6 ]/DNA mixture at 0.4 GPa (Figure 3b) show smaller frequency shifts under compression. Previous studies [26][27][28] revealed that high pressure can enhance the cluster structure interaction and lead to a band frequency shift. The hydrogen-bond network of an IL cluster structure may be disrupted, as some added molecules (such as DNA) may disturb the associations of ILs or cut large aggregations to small pieces.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1a shows two imidazolium peaks at 3124 and 3169 cm −1 , which correspond to the vibrational absorption bands of C 2 -H and C 4,5 -H on the imidazolium ring, respectively [26][27][28]. The other three bands in the region of 2850-3000 cm −1 in Figure 1a are assigned to the alkyl C-H vibrational modes on the cation tail of pure [26][27][28]. The curve fitting and deconvolution of pure ionic liquids spectra were performed with Lorentzian peaks.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations